Impact of lifestyle intervention in primary prevention of Type 2 diabetes did not differ by baseline age and BMI among Asian‐Indian people with impaired glucose tolerance. Issue 12 (12th February 2016) - Nanditha, A.; Snehalatha, C.; Ram, J.; Selvam, S.; Vijaya, L.; Shetty, S. A.; Arun, R.; Ramachandran, A.
Abstract: Aim: To investigate whether the effectiveness of lifestyle interventions on the incidence of diabetes was influenced by the baseline age and BMI of the Asian‐Indian participants with prediabetes. Methods: Pooled data, obtained from two of our Indian Diabetes Prevention Programmes (2006, n =236 and 2013, n =473; total N =709) which had similar baseline characteristics and intervention principles, were analysed. For the present secondary analysis we dichotomously categorized the participants' baseline age (<45 and ≥45 years) and BMI (<25.0 and ≥ 25.0 kg/m 2 ). Glycaemic status was ascertained at 6‐monthly intervals by oral glucose tolerance tests. The incidence rates of diabetes and relative risk reduction in both the intervention and the control group were calculated for categories of baseline age and BMI. Interactions between the intervention and baseline age and BMI on diabetes risk were also analysed. Results: Incident diabetes was diagnosed in 227 of the total 709 participants (32.0%) [control group 139 participants (38.8%) vs intervention group 88 participants (24.2%)] during the median follow‐up period of 2 years. The overall relative risk reduction was 35.4% (95% CI 19.3–48.3). Lifestyle intervention was equally effective in both age groups [relative risk reduction in those aged <45 years: 43.7% (95% CI 19.8–60.5) and in those aged ≥ 45 years: 28.9% (95% CI 5.3–46.6) P for interaction = 0.52] and in categories of BMI [BMI <25 kg/m 2 : 36.1% (95% CI 9.5–54.9); and BMI ≥ 25 kg/m 2 : 34.8% (95% CI 12.9–51.2); P for interaction = 0.95]. Conclusions: In Asian‐Indian individuals with prediabetes, the effectiveness of lifestyle intervention was not modified by baseline age and BMI. What's new?: In Western diabetes primary prevention programmes the effectiveness of lifestyle intervention has been shown to be influenced by baseline BMI and age. The present study assessed the effectiveness of lifestyle intervention on the incidence of diabetes among Asian‐Indian people with impaired glucose tolerance, stratified by age and BMI. The results showed that the impact of lifestyle intervention was similar among non‐obese and obese Asian‐Indians with impaired glucose tolerance in different age categories